PENGARUH PRAKTIK TATA KELOLA PERUSAHAAN TERHADAP KEPUTUSAN STRUKTUR MODAL DENGAN VARIABEL MODERASI KERAGAMAN GENDER (Studi Empiris pada Perusahaan Non Keuangan yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2019) - Tri Endrawati, Melati Wahyu; Arfinto, Erman Denny (Diponegoro Journal of Management, 2021)
ABSTRACT This study examines the effect board of directors size, board of commissioners size, independent commissioner, and audit committee as a proxy for corporate governance on leverage as a proxy for capital structure decisions. Gender diversity is added to moderate the relationship between corporate governance and capital structure. The purpose of this study is to find empirical evidence about (a) the effect the size of the board of directors on the level of leverage, (b) the effect the size of the board of commissioners on the level of leverage, (c) the effect of independent commissioners on the level of leverage, (d) the effect of the audit committee on the level of leverage, and (e) the influence of the moderating role of gender diversity in the relationship between corporate governance and capital structure. The sample in this study were non-financial companies listed on the Indonesia Stock Exchange in 2017-2019. Sampling using purposive sampling method. The sample of this research is 59 companies with 174 observations. Data analysis used multiple linear regression analysis for hypotheses 1-4 and Moderated Regression Analysis (MRA) for hypotheses 5-8. The results of the study using multiple linear regression analysis show that the size of the board of directors has a negative and significant effect on the level of leverage, but the size of the board of commissioners and independent commissioners has a positive and significant effect on the level of leverage. Meanwhile, the audit committee has no significant effect on the level of leverage. The results of the moderating variable study with MRA show that the interaction between the size of the board of directors and gender diversity on the level of leverage has a negative and significant effect. Meanwhile, the interaction between the size of the board of commissioners, independent commissioners and audit committee with gender diversity on the level of leverage does not have a significant effect.